TINJAUAN HUKUM ISLAM TERHADAP POLITIK DINASTI - Karunia, Ayu Fajri; Sohrah, Sohrah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
Dynastic politics has always reaped pros and cons, the pro side thinks dynastic politics is not contrary to democratic principles, but the contra side regards dynastic politics as a tool for maintaining power. This study aims to find out how Islamic law views dynastic politics, especially in Balleanging Village, Ujung Loe District, Bulukumba Regency. The research methods used are field qualitative, with juridical, historical, and syar'i approaches. The results showed that historically, the leadership relay in Balleanging Village had used dynastic politics, especially during the Gallarang-an period. Meanwhile, when using a democratic system, it was recorded that there had been a transition of leadership in one lineage, namely from Bundu Boto (1965 - 1993) which was replaced through the election process by Djohan Boto (1993 - 2007), and both were considered village heads who succeeded in building Balleanging Village. The Quran and the leadership practices of the Messenger of Allah do not specifically regulate the ideal system of government, only affirm the basic principles of leadership such as siddiq, tabligh, amanah, and fathanah, and the political history of Islam after the leadership of the Prophet and the khulafaurrasidins, recorded as having used dynastic politics, namely during the reigns of the Bani Ummayah and the Abbasids.